The Effect of UIUX Design of Artificial Intelligence E-Learning System on Student Learning Engagement - Erna Piantari; Sidiq Nugraha; Enjun Junaeti; Erlangga Erlangga (CCIT Journal, 2023)
Currently, e-learning has been widely used in the learning process. This is inseparable from the advantages of e-learning which allows learning to be done anytime, anywhere even with minimal instructor involvement or even no instructor involvement. The challenge in developing e-learning is how the learning process remains interesting and motivates students to remain fully involved in the learning process. In this study evaluated how the effect of UI/UX design on e-learning on AI learning that has been designed in previous research on learning engagement. The evaluation process was carried out comparing the value of student engagement in the previous AI e-learning with AI e-learning that had implemented the UI/UX design that had been designed. The value of student engagement is measured using the Online Student Engagement (OSE) matrix for skill and emotional indicators. Based on the results of the evaluation, it was concluded that UI/UX design can increase learning engagement on e-learning AI that was built with an average increase of 10.13% for skills indicators and 11.12% for emotional indicators.